Strategies for strengthening the numerical literacy of prospective mathematics teachers: An evaluation study - Effendi, Moh. Mahfud; Cahyono, Hendarto; Ummah, Siti Khoiruli; Yohanie, Dian Devita (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2025)
The urgency of this research is based on the phenomenon of the Minimum Competency Assessment (AKM), which has so far only involved students and teachers in schools. To date, there has been no national assessment specifically designed for prospective mathematics teachers, even though numeracy literacy is an essential competency for teacher candidates. Therefore, this study aims to describe the strategies for strengthening numeracy literacy among prospective mathematics teachers and to evaluate their implementation outcomes. This study employed a descriptive method with a mixed-methods approach. Quantitative analysis was conducted using literacy and numeracy test results to measure differences between first-year and third-year students, while qualitative analysis was based on interviews with lecturers to explore the strategies previously implemented to strengthen numeracy literacy. The results revealed that lecturers implemented several strategies, including independent project assignments, reading tasks followed by presentations, and exercises to complete incomplete information on lecture topics. Statistical tests indicated a significant difference between the literacy and numeracy skills of first-year and third-year students. The interview findings suggested that this difference was influenced by the higher mastery of basic mathematical concepts and a better understanding of mathematical reasoning among third-year students. This study contributes to the field of mathematics education by offering alternative strategies to enhance numeracy literacy among prospective mathematics teachers as a foundation for developing literacy- and numeracy-based university courses.